Decentralized and cost-effective colorimetry analysis by smartphone-based method digital image for monitoring electrochemical elimination of dye from water matrices - Cardozo, Jussara C.; Barbosa Segundo, Inalmar D.; de Medeiros Leandro, Maria Eduarda; Gondim, Amanda D.; Cavalcanti, Livia N.; dos Santos, Elisama V.; Martínez-Huitle, Carlos A. [UNESP] (Springer Nature, 2025)
The present research provides a newly developed method that aims at versatile, rapid, portable, and low-cost instrumental protocol for colorimetric analysis of waters, polluted by dyes, through the use of a smartphone and app that detects and represents the RGB (red, green, and blue) color model. The calibration of the method is based on RGB values obtained by capturing images of colored solutions with known concentrations. The method was spectrophotometrically validated by analyzing the same samples, reaching more than 95% of accuracy. The utilization of this smartphone-based method for colorimetric analysis was proposed to follow, for the first time, the electrochemical treatment of different water matrices (400 mL of synthetic and real) with substantial organic and salts content (50 mg L−1 of methylene blue in 0.1 mol L−1 Na2SO4) using boron-doped diamond (BDD) anode by applying current densities (j) of 15, 30, and 60 mA cm−2. Discoloration results (which were achieved with this novel smart water security solution) clearly showed that significant removal efficiencies were achieved in 2 h, depending on the j, when synthetic and real effluents were used. A key role was played by the sulfates in solution which were electroconverted to persulfates via reaction with •OH produced at BDD surface, enhancing the oxidation power of the electrochemical treatment. Then, the procedure presented here obtained a high level of confidence representing great support for scientific laboratories as an alternative that can replace the use of expensive spectrophotometers.
Keywords: Digital image colorimetry; Digitalization; RGB image processing; Smartphone-based technology